2012
DOI: 10.1109/titb.2012.2207400
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology for Validating Artifact Removal Techniques for Physiological Signals

Abstract: Abstract-Artifact removal from physiological signals is an essential component of the biosignal processing pipeline. The need for powerful and robust methods for this process has become particularly acute as healthcare technology deployment undergoes transition from the current hospital-centric setting toward a wearable and ubiquitous monitoring environment. Currently, determining the relative efficacy and performance of the multiple artifact removal techniques available on real world data can be problematic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 19 publications
0
75
0
Order By: Relevance
“…The data for both modalities was recorded independently using the novel recording methodology proposed in [25]. This particular recording methodology is capable of producing two highly correlated signals for each modality.…”
Section: G Data Acquisitionmentioning
confidence: 99%
“…The data for both modalities was recorded independently using the novel recording methodology proposed in [25]. This particular recording methodology is capable of producing two highly correlated signals for each modality.…”
Section: G Data Acquisitionmentioning
confidence: 99%
“…While EEG provides a measure of neural electrical activity, by contrast fNIR measures blood oxygenation levels via infrared light (e.g., Izzetoglu et al, 2007; Ayaz et al, 2009, 2011, 2012a,b,c). In essence, fNIR can provide different and complementary biological markers for brain dynamics with increased robustness to artifacts during cognitive and motor performance under everyday conditions and in real life environments (e.g., Coyle et al, 2007; Hatakenaka et al, 2007; Leff et al, 2008a,b; Abdelnour and Huppert, 2009; Ayaz et al, 2009, 2011, 2012a,b,c; Gentili et al, 2010a; James et al, 2010, 2012; Power et al, 2012; Sweeney et al, 2012). Comparatively, it was demonstrated that fNIR could indicate various levels of cognitive workload (Izzetoglu et al, 2005; Ayaz et al, 2009, 2012a,b,c; James et al, 2012; Power et al, 2012) as well as changes in motor performance (Hatakenaka et al, 2007; Ikegami and Taga, 2008; Leff et al, 2008a,b; Morihiro et al, 2009; Gentili et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…More enhanced algorithms can aggregate to the quality measurement higher statistical moments, or abnormal skewness or Kurtosis values [53]. In addition, the artifact detection algorithm can incorporate knowledge about invalid postures, using a priori constraints of the human body [54], about the operation range (if it resides in the optimal coverage), and about the features that are derived by interpolation, mainly when parts of the human body are out of the Kinect frame.…”
Section: Methodsmentioning
confidence: 99%